Molecular, Cellular, and Tissue Engineering of the Vascular System (Advances in Experimental Medicine and Biology,, 2018)
This book introduces the latest research in molecular, cellular, and tissue engineering of the vascular system. Topics covered include the roles of endothelial surface glycocalyx as a mechano-sensor and transducer for blood flow, a barrier to water and solute transport across the vascular wall and to the interaction between circulating cells and the vessel wall, the roles of nuclear envelope proteins and nuclear lamina in regulating vascular functions under blood flow-induced forces, and the roles of smooth muscle cells and extracellular components in arterial vasoconstriction. Other topics covered include non-surgical vascular interventions for coronary artery diseases, genesis and mechanisms of atherosclerotic plaque microcalcifications and human abdominal aortic aneurysms, experiments and modelling for red blood cell and tumor cell movement in microcirculation, transport across the blood-brain barrier and its role in Alzheimer's disease, mathematical models for cell survival after hyperthermia, application of hypothermia in enhancing treatment for brain and spinal cord injuries, and damage of eardrums due to blast waves. This is an ideal book for biomedical engineers and researchers, medical researchers, and students in biomedical engineering and medical sciences.